2022
DOI: 10.1111/jopy.12719
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal bidirectional associations between personality and becoming a leader

Abstract: Leaders play a crucial role in organizational success and growth. They take landmark decisions, manage different projects and teams, and ideally inspire and support their subordinates to fully unfold their potentials. According to previous research, leadership success not only depends on professional expertise but also on personality (Bono &

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 69 publications
(138 reference statements)
0
8
0
1
Order By: Relevance
“…Similar to previous publications (Asselmann et al, 2022;Denissen et al, 2019), we used multilevel analyses with measurement occasions (Level 1) nested within persons (Level 2) and built separate models for life satisfaction, happiness, sadness, anxiety, and anger.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to previous publications (Asselmann et al, 2022;Denissen et al, 2019), we used multilevel analyses with measurement occasions (Level 1) nested within persons (Level 2) and built separate models for life satisfaction, happiness, sadness, anxiety, and anger.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is evidence of all three issues playing a role in explaining why there are fewer women than men in organizational-leadership role. As noted above, Asselmann et al (2023) highlighted the issue of agency and aspiration, suggesting that women are less likely to apply for, and therefore get elected to, leadership roles. There is also an extensive literature on sex differences in personality and intelligence, which has generally suggested mostly small differences (Furnham & Treglown, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…There is also the issue of reciprocal or bidirectional causality in this area. Hence, Asselmann et al (2023), in addressing the fundamental problems of change in leadership, concluded that people are not simply "born to be leaders" but that their personalities can and do change in preparation for a leadership role and due to actual leadership experience. They established that leaders-to-be were more extraverted, open, emotionally stable, conscientious, willing to take risks, felt to have greater control, and trusted others more than nonleaders.…”
Section: Individual Differences In Leadershipmentioning
confidence: 99%
“…Using data from the SOEP, the authors previously examined changes in personality traits in the years before and after becoming a parent (Asselmann & Specht, 2021b), romantic relationship events (Asselmann & Specht, 2020a), the death of a partner (Asselmann & Specht, 2020b), the transition to work and retirement (Asselmann & Specht, 2021a), and becoming a leader (Asselmann et al, 2023). They also investigated changes in subjective well-being in the years before and after becoming a parent (Asselmann & Specht, 2023a), romantic relationship events (Asselmann & Specht, 2022a), the death of a loved one (Asselmann & Specht, 2022b), and becoming a leader (Asselmann & Specht, 2023b).…”
Section: Overlap With Previous Publicationsmentioning
confidence: 99%